Party responses to social movements : challenges and opportunities - Piccio, Daniela R. (Protest, culture and society, 2019)
Across the West, the explosion of social movement activity since the late 1960s has constituted a "participatory revolution" that has posed profound challenges for formal political parties. Through an analysis of new interviews, institutional documents, and a host of other largely unexploited sources, Daniela R. Piccio provides a rich and empirically grounded exploration of the wide-ranging responses to these movements. Focusing on Italy and the Netherlands since the 1970s, Party Responses to Social Movements demonstrates how political parties have incorporated the demands of movements to a surprising extent, even as both have grappled with fundamental and inevitable tensions between their respective roles and aims.